A zene analitikus restrukturálása - Ertüngealp, Alpaslan (Kultúratudományi Szemle, 2022)
In this study, we find an introduction to the debate on causation in relation to sounds, in which I explore the conditions underlying the debate and its framework. In my further formulations, which relies on one side on the Critiques of Kant and on the other side on analytical philosophy, I subject scientific (physics- and neuroscience-based) knowledge and theories related to musical phenomena (which are not included in this paper and are presented in several chapters of my dissertation) to metaphysical analysis and examine these within the mind of the subject. Finally, I present a new meaning to the concept of music in its new structure, attempting at analytical restructuring.